Los materiales educativos y desarrollo de habilidades motrices en niños y niñas de cuatro y cinco años de la Institución Educativa Inicial Las Colinas N° 317 en el Distrito de San Juan Bautista 2022 - Mori Moreno, Jenifer (2024)
The research is titled educational materials and development of motor skills in four- and five-year-old boys and girls of the Initial Educational Institution N° 317 Las Colinas, district of San Juan Bautista 2022, applied an orientation to a quantitative research seeking to know the relationship of the study variables, focusing on a descriptive, correlational, non-experimental design in a sample of 168 students, who were selected from four and five year old classrooms, relying on probabilistic sampling, using data collection instruments aimed at obtain relevant information on the study variables. Those results presented allow us to observe the relationship between educational materials and motor skills that focus on important scenarios in the cognitive development of students. The correlation statistic applied was the student's t with a significance level of 5% and a Kolmogorov-Smirnov goodness of fit test for the variables "educational materials" and "Development of motor skills" with a probability<0.05, rejecting the null presumption and affirming the alternative presumption, the research concludes by stating that both variables do not fit a normal distribution and as a consequence the analysis of the theory will use non- parametric tests such as Spearman's rho for contrast with the t test statistic. Student with n-2 degrees of freedom. Concluding the research in a statement that a union is observed between the study variables in the student population focused on and used for this research.